Adaptive Medical Image Watermarking Technique based on Wavelet Transform - Abdullah, Nada; Abduljaleel, Mohammed (Iraqi Journal of Science, 2023)
In this paper, an adaptive medical image watermarking technique is proposed based on wavelet transform and properties of human visual system in order to maintain the authentication of medical images. Watermark embedding process is carried out by transforming the medical image into wavelet domain and then adaptive thresholding is computed to determine the suitable locations to hide the watermark in the image coefficients. The watermark data is embedded in the coefficients that are less sensitive into the human visual system in order to achieve the fidelity of medical image. Experimental results show that the degradation by embedding the watermark is too small to be visualized. Also, the proposed adaptive watermarking technique can preserve the fidelity of medical image. The fidelity performance of proposed technique was evaluated by three image quality metrics are PSNR, UQI and SSIM. The evaluation results exhibit the high results of the proposed technique respect with fidelity of medical image.